A Rechargeable, Aqueous Iron Air Battery with Nanostructured Electrodes Capable of High Energy Density Operation. Issue 6 (31st March 2017) - Figueredo-Rodríguez, H. A.; McKerracher, R. D.; Insausti, M.; Luis, A. Garcia; de Leόn, C. Ponce; Alegre, C.; Baglio, V.; Aricò, A. S.; Walsh, F. C.
Abstract : In order to decrease the global dependence on fossil fuels, high energy density, rechargeable batteries with high charge capacity are required for mobile applications and efficient utilization of intermittent sources of renewable energy. Metal-air batteries are promising due to their high theoretical energy density. In particular, the iron-air battery, with a maximum specific energy output of 764 W h kg −1 Fe, represents a low cost possibility. This paper considers an iron-air battery with nanocomposite electrodes, which achieves an energy density of 453 W h kg −1 Fe and a maximum charge capacity of 814 mA h g −1 Fe when cycled at a current density of 10 mA cm −2, with a cell voltage of 0.76 V. The cell was manufactured by 3D printing, allowing rapid modifications and improvements to be implemented before an optimized prototype can be manufactured using traditional computer numerical control machining.